FUNCTIONAL REQUIREMENTS FOR INFORMATION SYSTEMS ELECTRONIC DOCUMENT CIRCULATION (Journal of history, 2019)
The article deals with the emergence and improvement of functional requirements for information systems of electronic document management. The authors analyze the current requirements of international communities to the electronic document management systems. The content and requirements of ISO 15489 are disclosed. The efficiency and wide acceptance of the European specification MoReq MoReq is determined. The need for independent testing of systems will be justified. Legal documents in the Russian Federation on requirements of information systems of electronic document circulation and its practice are stated. The complex of requirements and its position to the electronic document management is shown.